ORGANIZATION OF STUDENT SELF-GOVERNMENT IN MODERN UKRAINIAN SCHOOL: MOTIVATION AND INCENTIVES STUDENTS - Alokhin Mykhailo М. (Educological discourse, 2015)
The article is dedicated to the problem of the organization of the student government at modern general educational establishments in Ukraine. The problem of student motivation was considered by the author and it were defined the types and mechanisms of the student’s promotion as a background of their activity in the functioning of the student government. It were proposed the main measures of the moral and material incentives for the leaders among students , was studied and summarized the experience of the stimulating students at secondary schools of Ukraine. The statistical results of the research of the effectiveness in using different kinds of the promotion of pupils who participate in the student government bodies were represented according to the type, scope, validity.